INSTITUTIONAL MECHANISMS OF PUBLIC MANAGEMENT OF THE DEVELOPMENT OF THE CONSTRUCTION INDUSTRY IN THE CONDITIONS OF DECENTRALIZATION - TOPAZLY, Roman (Herald of Khmelnytskyi National University. Economic sciences, 2025)
The article carries out a comprehensive study of institutional mechanisms of public management of the development of the construction industry in the context of decentralization, which is becoming particularly relevant in the context of reforming the system of territorial organization of power in Ukraine. The content of the concepts of "public management", "institutional mechanisms", "construction industry" and "decentralization" is revealed, their interrelationships and place in modern public administration are determined. Particular attention is paid to the analysis of the impact of decentralization processes on the transformation of construction management tools at the local level. It is argued that the transfer of powers and financial resources to local self-government bodies requires the formation of new approaches to the regulation of construction activities, strengthening the institutional capacity of communities and establishing effective intersectoral interaction. The study outlines the key elements of the institutional support of public management in the construction sector, including the regulatory framework, budget policy, organizational and managerial structures and tools of public participation. The main challenges were identified, in particular, staff shortages, uneven financial support for communities, fragmentation of the legislative framework, and directions for improving management mechanisms were proposed, including: improving professional training of personnel in the field of urban development, creating electronic systems for monitoring construction projects, attracting international expertise and investments. Based on the analysis of the domestic regulatory framework, statistical data, and modern practices of local government, conclusions were drawn regarding the need to integrate strategic planning for territorial development with spatial development plans and the formation of an effective system of multi-level governance in the construction industry. The research materials can become the basis for developing new management solutions aimed at ensuring the sustainable development of the construction industry as one of the key sectors of the national economy in the context of decentralization.
Keywords: construction industry; public administration; decentralization; institutional mechanisms; local self-government